2022
DOI: 10.1007/s00234-022-03004-w
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of cerebral arterial vasospasm following aneurysmal subarachnoid haemorrhage: a systematic review and meta-analysis

Abstract: Purpose To describe a pooled estimated incidence of cerebral arterial vasospasm (aVSP) following aneurysmal subarachnoid haemorrhage (aSAH) and to describe sources of variation in the reported incidence. Methods We performed a systematic review and meta-analysis of randomised clinical trials (RCTs) and cohort studies. The primary outcome was the proportion of study participants diagnosed with aVSP. We assessed for heterogeneity based on mode of imaging, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies have reported an incidence of cerebral vasospasms between 9% and 93%. 1 The broad range of reported incidences might be due to the non-uniform definition of cerebral vasospasms. Most studies used CTA, DSA or elevated flow profiles in TCD to confirm cerebral vasospasms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported an incidence of cerebral vasospasms between 9% and 93%. 1 The broad range of reported incidences might be due to the non-uniform definition of cerebral vasospasms. Most studies used CTA, DSA or elevated flow profiles in TCD to confirm cerebral vasospasms.…”
Section: Discussionmentioning
confidence: 99%
“…In this single-center, retrospective study we included all patients who were treated at our tertiary stroke center with aSAH in the time between January 2016 and December 2022. Inclusion criteria were as follows: (1) acute SAH due to a ruptured intracranial aneurysm and (2) age >18 years. Exclusion criteria were (1) SAH due to other causes or without evidence of ruptured aneurysm, (2) death within 14 days after symptom onset without the evidence of relevant vasospasms or vasospasm-related infarction, and (3) missing data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations